Asymtotical expansions in local limit theorem of large deviations - Skrabutėnas, Rimantas (Lietuvos matematikos rinkinys, 2002)
We continue investigation of the local distribution of multiplicative arithmetic functions from the class M(G). In the present paper the local limit theorem of large deviations with asymptotical expansion of the principal term is obtained.